Prosocial Behavior And Determinants In The Accountability Of Village Fund Management - Rani Eka Diansari; May Dina Triastuti; Vidya Vitta Adhivinna; Ratna Purnama Sari; Anandita Zulia Putri (UNIB Press, 2024)
The purpose of this study is to investigate the impact of village's official competency, application of the village financial system, community participation, prosocial behaviour, and external pressure on village fund management accountability. This study's population includes the entire village administration of Sleman Regency. This study is conducted in 17 villages that represent each district with the largest village fund gain under Sleman Regent Decree Number 2/Kep.KDH/A/2021 related to The Amount of Village Fund of 2021. This study used the purposive sampling method. The sample for this study consists of 106 village government officials who are active in managing village funds in accordance with the Minister of Home Affairs of the Republic of Indonesia Regulation 20 of 2018 on village fund management. This research is quantitative. This study employed primary data, which was collected utilizing questionnaires. This study's data analysis methods included descriptive statistics, data quality, and hypothesis testing. The findings of this study reveal that Village's official competency, application of the village financial system, community participation, prosocial behaviour, and external pressure all have a major impact on the accountability of village fund management.